Efektifitas Teknik Terapi Pernapasan Buteyko Pada BPK.W Dengan Asma Dalam Memperbaiki Pola Napas - Mesi Maesaroh; Rina Puspita Sari; M.Hasan Basri; Alfika Safitri (An-Najat, 2023)
Families with adult children or discharge are the stages that begin when the first child leaves the house. Asthma is an obstructive airway disease characterized by narrowing of the airways. Narrowing of the airway will result in the patient experiencing dyspnea, coughing, wheezing. . The number of bronchial asthma sufferers in Indonesia is almost 14.5 million people, of which about 20% are suffered by children aged 6-12 years. The Buteyko breathing technique can reduce the frequency of asthma attacks, their recurrence and prevent their severity. Objective: to determine the effect of Buteyko breathing technique therapy on reducing symptoms in asthma patients. Method: by means of interviews and conducting assessments. Results: The case study was obtained after the client was given Buteyko breathing technique therapy to reduce asthma symptoms in Mr. W significant results, where there was a decrease in asthma symptoms which reduced tightness RR value from 26x/min to 20x/min. Conclusion: The Buteyko breathing therapy technique has an effect on improving breathing patterns in patients with asthma or shortness of breath.